Analisis Konten Animasi 2D Lagu Anak Indonesia Balita Sebagai Sarana Edukasi Anak dalam Platform Youtube (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2025)
Visual communication is an effective way to convey messages, especially in the context of delivering messages for the development of children's character. Beneficial visual content can help shape the values and perspectives of children. By controlling the consumed content, we can ensure a positive learning experience for children. Paying attention to the visual content provided to children is a crucial step in creating an environment that supports their positive growth. This journal explains how an animated children's song becomes an educational tool broadcasted through the YouTube platform. By combining careful theoretical and research methodology approaches, this journal explores how animated content on YouTube can serve as an educational tool for children. The results of this study will create an understanding of an easily accessible educational tool for children through the YouTube platform. The discussion of this topic can provide valuable insights to support the effective design of animated content in aiding the developmental stages of children